Treatment of tinea corporis with Tacca chantrieri's extract - Rujjanawate, Chaiyong (Creative Science, 2016)
Tinea corporis is usually treated by antifungal agents which are chemicals that are not produceddomestically and have to be imported. The use of indigenous herbs, if possible, would be a sustainable solution.We therefore established a double blind study to evaluate a short term treatment of tinea corporis with the extract of Tacca chantrieri, a local herb found in many parts of Thailand. Eighty patients were randomly selected to apply tacca extract or the base solution alone for 14 days, and the lesions were periodically assessed on day 0, 7, 14 and 42. Each assessment consisted of clinical evaluation of redness, scaling and pruritus and direct microscopy examination. The extract recipients showed significant clinical mycologic improvement beginning at day 7 through day 14. Microscopic examination of the skin scrapings showed negative results in all extract recipients on day 14. Clinical evaluation and microscopic examination on day 42 indicated some mycologic infections in both control and test groups. It was concluded that the extract of Tacca chantrieri could be used as an effective agent to treat tinea corporis. However, recurrent infections after the cessation of treatment are possible.